DESEMPENHO ZOOTÉCNICO DE CURIMBAS EM SISTEMA DE RECIRCULAÇÃO DE ÁGUA E AQUAPONIA. - MENDEZ, Victor Hugo Benassi,; NETO, Nilton de Magalhães,; ACUNHA, Rubia Mara Gomes,; WANDERLEY, Alysson Martins,; ALMEIDA, Rômullo Guilherme dos Santos,; MELDAU, Cristiane de Campos, (ANAIS DO ENIC, 2024)
-